Macrobenthic response to sewage discharges in confined areas from coastal lagoons: implication on the ecological quality status - Piló, David (2011)
We studied the effect of wastewater on macrobenthic assemblages and local Ecological Quality Status (EcoQS) along a pollution gradient. The study consisted of six sampling sites surrounding the discharge channel of a Wastewater Treatment Plant located within Ria Formosa coastal lagoon. The total number of individuals was significantly higher at the discharge point comparatively to the control site, while total number of species, species richness and diversity values revealed the opposite pattern. Deposit-feeding were the most abundant trophic group, particularly at the inner sites, while the highest contributions of suspension-feeding and carnivory groups were observed at external ones. The organic matter content was positively correlated with the deposit-feeding group conferring a structural character of this variable near the plant discharge. M-AMBI index was consistent with the ANOSIM and SIMPER analysis, successfully separating the sampling stations according to the distance from the discharge and distinguishing the lower EcoQS of the inner sites not complying with the requirements of the Water Framework Directive of a “Good” quality status. In addition, changes in ecological and biotic indices were negatively correlated with variations of organic matter and positively correlated with salinity, corroborating the effect of these variables on the composition and structure of macrobenthic communities.